2016
DOI: 10.1007/s12178-016-9356-5
|View full text |Cite
|
Sign up to set email alerts
|

C1 fractures: a review of diagnoses, management options, and outcomes

Abstract: The atlas is subject to fracture under axial load, often due to traumatic injuries such as shallow dives and automobile accidents. These fractures account for 2-13 % of injuries to the cervical spine [Marcon RM et al. Clinics (Sao Paulo) 68(11):1455-61, 2013]. Fractures of the C1 vertebra are often difficult to diagnose, as there is often no neurological deficit or easily identifiable findings on radiographs. However, injuries to the atlas can be associated with vertebral artery injury and atlantoaxial or atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 32 publications
1
31
0
2
Order By: Relevance
“…In this context, it must be noted that the decision for and the type of surgery was frequently made based on concomitant injuries of the adjacent cervical spine segments. The in-hospital complications observed in this study were in the range of what is known from other case series [1,10]. Nosocomial infections as well as the development of a delirium must be considered as high-risk complications after surgery of elderly patients.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In this context, it must be noted that the decision for and the type of surgery was frequently made based on concomitant injuries of the adjacent cervical spine segments. The in-hospital complications observed in this study were in the range of what is known from other case series [1,10]. Nosocomial infections as well as the development of a delirium must be considered as high-risk complications after surgery of elderly patients.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast to the literature, however, almost every fourth Gehweiler 4 fracture in our population was treated operatively. The literature mainly recommends conservative treatment for isolated fractures of the lateral masses [10]. However, recent studies observed frequently a lateral displacement of the lateral mass fragments associated with subluxation of the occipital condyle resulting in neck pain, head malposition and impaired head rotation [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on ratings of experienced spine surgeons, the aims of this study were to evaluate (1) the interobserver reliability of the Gehweiler classification and (2) the C1-fracture stability as well as (3) to assess treatment strategies according to their prior fracture classification.…”
Section: Introductionmentioning
confidence: 99%
“…The atlas has two lateral masses with concavities that match the condyles of the occiput and the dens of the axis, forming the occipito-atlantoaxis complex. The occipito-atlanto-axis complex provides approximately 50% of its lateral rotation and exion-extension of the entire cervical spine [2]. In order to preserve the mobility of occipito-atlanto-axis articulation, direct posterior C1 pedicle screw xation of unstable fractures of the atlas has been reported.…”
Section: Introductionmentioning
confidence: 99%